Effect of Elephantopus scaber.L and Polyscias obtusa Leaf Extract for CD8+ and CD8+CD62L+ T Cell Modulation in Balb/c Mice - Nurul Faizah; Muhammad Sasmito Djati (University of Brawijaya, 2014)
Medicinal herbal is highly recommended especially for pregnant women with bacterial infection to reduce the consumption of synthetic antibiotics that are harmful to their body and also fetus. E. scaber and P. obtusa are believed to increase the number of imunocompetent cells such as CD8+ and CD8+CD62L+ T cell cause both plants have biochemical compound such as saponin and flavonoid. These plants good for immune system, but optimum dose of mixture extracts from both leaves to increase the number of CD8+ and CD8+CD62L+ T cell in mice is doesnt know yet. This study to determine effect of E. scaber and P. obtusa leaf extract by compared the number of CD8+ and CD8+CD62L+ T cell between control mice and treated mice. E. scaber and P. obtusa leaf extract can not reduce relative number of CD8+ T cells compared with control mice after 14 days treatment and 18 days. Even it show little different number but it was not significantly different, whereas the number of CD8+ decreased in K2 control mice also not significantly different than other treatments. K1 group is always show the highest number of CD8+ T cell compared to other treatments. CD8+ was decreased by increasing the doses of P. obtusa leaf extract. Key word: E. scaber, CD8+ T cell, CD8+CD62L+ T cell, P. obtusa, Salmonella typhimurium.